Covalent Functionalization of Carbon Nitride Frameworks through Cross‐Coupling Reactions. Issue 56 (7th September 2018) - Sun, Jingwen; Phatake, Ravindra; Azoulay, Adi; Peng, Guiming; Han, Chenhui; Barrio, Jesús; Xu, Jingsan; Wang, Xin; Shalom, Menny
Abstract: A new and simple synthetic route is introduced to covalently functionalize the carbon nitride (CN) framework by the implementation of halogenated phenyl groups (Cl, Br and I), which serve as a chemically reactive center, within the CN framework. The covalent modification is demonstrated here by substituting phenyl and tert ‐butyl propionate onto the modified‐CN framework through Suzuki and reductive‐Heck cross‐coupling reactions, respectively. The effective functionalization leads to a facile exfoliation of the CN framework into thinner layers and greatly enhances the dispersibility in many solvents as well as the photocatalytic activity compared to the unmodified CN. The general covalent modification opens the possibility for tailor‐made design of dispersible CN materials, including their photophysical and chemical properties, toward their exploitation in many fields, such as photocatalysis, bio‐imaging, sensing, and heterogeneous catalysis. Abstract : A new, general synthetic route to covalently functionalize carbon nitride based semiconductors by the implementation of halogenated phenyl groups (Cl, Br and I), which serve as a chemically reactive center, within the CN framework is reported. The effective functionalization greatly enhances its dispersibility in many solvents as well as the photocatalytic activity.